Mitogenomic evidence reveals the phylogeography of Sulawesi Actenoides kingfisher linked to geological barriers - Yohanna Yohanna; Anik Budhi Dharmayanthi; Karen M. C Rowe; Rachael L. Joakim; Rauri C. K. Bowie; Andrew Engilis; Luke Bloch; Tri Haryoko; Dewi Malia Prawiradilaga; Noviar Andayani; Jatna Supriatna (BRIN Publishing (Penerbit BRIN), 2026)
The genus Actenoides (Alcedinidae) comprises brightly colored kingfishers endemic to the Indo-Australian Archipelago. It provides a good model for exploring how geological and ecological factorshave shaped diversification across Wallacea. Sulawesi has the highest diversity of Actenoides comparedto single-island representatives elsewhere. We aimed to study the phylogenomics of Actenoides acrossIndonesia, particularly in Sulawesi, to reveal evolutionary divergence associated with their endemicityusing the mitogenome. Phylogenomic relationships were reconstructed using Maximum Likelihood inIQ-TREE. Phylogenomic relationships inferred from Maximum Likelihood in the IQ tree showeddivergence between Sulawesi Actenoides and A. concretus, and between A. princeps and A. monachus,both supported by high bootstrap values. The genetic p-distance among those species inferred from theNJ tree showed genetic distances of around 8% between the Sumatra (A. concretus) and Sulawesilineages, and 6% between A. monachus and A. princeps. Furthermore, the population from northeasternSulawesi for both A. princeps and A. monachus showed early divergence from other populations; hence,it has deep and distinct lineages even from its closest sister populations in northwestern Sulawesi. Thesefindings highlight phylogenomic differentiation within Actenoides and emphasize the role of Sulawesi’scomplex geological history in promoting inland diversification of Wallacean birds.